Research on ciphertext search and sharing technology in edge computing mode - Jifeng WANG; Guofeng WANG (Tongxin xuebao)
Aiming at the problem of edge computing data security, a ciphertext search and sharing solution was proposed, where the above-mentioned edge computing advantages were used to achieve user privacy data protection, edge nodes were used to construct encrypted inverted indexes, indexes and keys between edge nodes and cloud computing platforms were securely shared, and ciphertext search, secure data sharing, and dynamic index update were realized without changing the edge computing architecture and cloud computing architecture.Finally, compared to existing schemes, performance and security were analyzed and discussed, which proves that the proposed scheme has high security strength under ciphertext search attack model, and the ciphertext search efficiency and document dynamic update function are taken into account based on encrypted inverted index.